Karakteristik Ibu Hamil dengan Hepatitis B di RSUD dr. Doris Sylvanus Palangka Raya periode Januari 2020 s/d Desember 2021 - Laga, Ardiles Robinson Rohi; Patricia, Tisha; Eka Shinta, Herlina (Fakultas Kedokteran Universitas Palangka Raya, 2023)
Hepatitis B is infectious disease caused by hepatitis B virus. Around 296 million people in the world diagnosed hepatitis B, and prevalence of hepatitis B in Indonesia was 0.40%. Screening for hepatitis B can be done through HBsAg test. To determine the characteristics of pregnant women with hepatitis B in RSUD dr. Doris Sylvanus Palangka Raya Period January 2020 to December 2021. Descriptive study where pregnant women with hepatitis B as the sample based on the medical record. The percentage of age, education level, occupation, gestational age, gravida, parity, and abortions in pregnant women with hepatitis B were found to be highest in the age group 26-35 years were 52% (31 people), primary education was 50% (30 people), housewife was 87% (52 people), third trimester was 94% (56 people), multigravida was 53% (32 people), parity 1 was 38% (23 people), abortion 0 was 72% (43 people). The characteristics of age, education level, occupation, gestational age, gravida, parity, and abortions in pregnant women with hepatitis B were found to be highest in the age group 26-35 years, primary education, housewife, third trimester, multigravida, parity 1, and abortion 0.